Evaluation of reflective cracking resistance in bituminous mixtures - Pais, Jorge C. (2000)
Bituminous overlays are currently the most prevalent method used to ret.:'1rd the reappearance of cracks in the pavement surface. Even though the usual distress mode in overlays is reflective cracking. the design of these overlays typically does not take tlus parlicular distress mecharlism into account. Oftentimes. reflective cracks rapidly propagate tlrrough the overlay, sometimes witllin a year or two of rehabilitation. Ideally. overlays should have the ability to retard, for some time, the propagation of the existing crack pattem The resistance of a bituminous mi:..1ure to reflective cracking can be evaluated by measuring the fatigue life of specimens in the laboratory under similar conditions 10 those occurring in actual pavements. The results of such laboratory fatigue tests could then be used in pavement design with a greater degree of confidence. In tlus paper. laboratory simulation of the cracking phenomena that takes place in the field is carried out with the Reflective Cracking Device (RCD). The RCD applies a typical crack activity pattern as can be directly measured in flexible pavements. A method for measuring the fatigue life of an overlay due to reflective cracking is proposed, based on the analysis of displacement control tests with the RCD. For the design of pavement overlays, a mechanistic-empirical method, which includes reflective cracking criteria. is proposed. This metilOd consists of an iterative process to find tile overlay thickness timt considers fatigue life due to reflective cracking.